(untitled) (Journal of Pathology of Nepal, 2020)
Background: Pap smear examination has been universally used as an effective screening tool for early detection of cervical carcinoma. The aim of this study was to assess the utility of Cervical Acid Phosphatase staining as an adjunct to routine Pap smear testing to improvethe sensitivity and specificity of routine Pap smear examination for cervical cancer detection. Materials and Methods: Cervical smears were taken from patients attending the gynecology department and a few cervical cancer screening programmes. One set of slides were alcohol fixed and stained with rapid pap stain and another set of slides were fixed in a special fixative and stained with Cervical Acid Phosphatase -Pap stain. The nuclear features of these Cervical Acid Phosphatase stained dysplastic cells was studied on Pap stain to diagnose cervical intraepithelial lesion/ malignancy. Results: Out of 489 cases included in the study 6 cases were diagnosed with intraepithelial lesion/ malignancy. On Cervical Acid Phosphatase -Pap stain 2 of the cases diagnosed as inflammatory smears on pap stain showed Cervical Acid Phosphatase positivity and thus were re evaluated. Mild nuclear atypia was observed in the Cervical Acid Phosphatase positive cells and these cases were diagnosed as Low grade squamous intraepithelial lesion and later biopsy proven to be Cervical intraepithelial Neoplasia I. Therefore Cervical Acid Phosphatase -Pap test was 100% sensitive and specific for cervical cancer detection. Conclusions: With 100% sensitivity Cervical Acid Phosphatase -Pap test satisfies the criteria of an efficient screening test.